2009
DOI: 10.1038/clpt.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Altered Systemic Exposure to Atorvastatin Acid Following Gastric Bypass Surgery in Morbidly Obese Patients

Abstract: The impact of gastric bypass on atorvastatin pharmacokinetics was investigated in 12 morbidly obese patients being treated with 20-80 mg atorvastatin each morning. Eight-hour pharmacokinetic investigations were performed the day before the surgery and at a median of 5 weeks (range 3-6 weeks) after the surgery. Gastric bypass surgery produced a variable effect on individual systemic exposure to atorvastatin acid (area under the plasma concentration vs. time curve from 0 to 8 h postdose (AUC(0-8))), ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 32 publications
7
81
0
Order By: Relevance
“…We have demonstrated that RYGB dramatically increased the rate at which oral morphine is absorbed in comparison with preoperative data. Skottheim et al [5,8] reported comparable C max and t max values for oral atorvastatin before and after RYGB in a similar series of patients, and Padwal et al [5,8] showed that the C max and t max values for metformin in patients who underwent an RYGB and those who did not were similar. The rates of gastric emptying for both liquid and solid markers are dramatically greater in patients with RYGB because of their small gastric pouch than in patients before RYGB, while the intestinal transit time is reduced, as recently demonstrated [30].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We have demonstrated that RYGB dramatically increased the rate at which oral morphine is absorbed in comparison with preoperative data. Skottheim et al [5,8] reported comparable C max and t max values for oral atorvastatin before and after RYGB in a similar series of patients, and Padwal et al [5,8] showed that the C max and t max values for metformin in patients who underwent an RYGB and those who did not were similar. The rates of gastric emptying for both liquid and solid markers are dramatically greater in patients with RYGB because of their small gastric pouch than in patients before RYGB, while the intestinal transit time is reduced, as recently demonstrated [30].…”
Section: Discussionmentioning
confidence: 79%
“…Only one compared drug pharmacokinetics at different times after RYGB [6]. It has been difficult to draw any general conclusion; the effects of some oral drugs remain unchanged or are increased (atorvastatin, moxifloxacin, metformin), while those of others are reduced (selective serotonin reuptake inhibitors), according to the post operative period [3][4][5][6][7][8][9][10]. It is therefore necessary to carry out controlled studies on each specific drug of interest to evaluate the specific effect of obesity and of RYGB on the pharmacokinetics of that particular drug.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…32,34,35 However, recent studies have shown contrasting results either because of altered bioavailability from decreased absorption or because of rapid transit or decreased first-pass metabolism from bypassing the drug-metabolizing enzymes in duodenum and proximal jejunum. 36,37 Skottheim et al 36 reported significantly altered systemic exposure to atorvastatin after RYGB, ranging from a 3-fold decrease to a 2-fold increase in AUC. However, this study was conducted within 6 weeks of bariatric surgery when the subjects were still undergoing rapid weight loss.…”
Section: Discussionmentioning
confidence: 98%
“…3 Some potential problems with drug absorption in the RYGB patient have been identified. 3,[9][10][11][12][13] However, little guidance is available on selecting therapeutic alternatives when drug absorption issues are identified in these patients. Utilizing the physiochemical properties of individual drugs or drug classes, such as the acid dissociation constant (pK a ), partition coefficient (log P), and intestinal drug transporters, practitioners may be able to recommend better drug therapy regimens for their RYGB patients.…”
mentioning
confidence: 99%